Changes in physical activity during transition to retirement: a cohort study. Issue 1 (December 2016) - Stenholm, Sari; Pulakka, Anna; Kawachi, Ichiro; Oksanen, Tuula; Halonen, Jaana; Aalto, Ville; Kivimäki, Mika; Vahtera, Jussi
Abstract Background Retirement is a major life transition which may affect lifestyle. The aim of this study is to examine within-individual changes in physical activity during the transition from full-time work to retirement. Methods The study population consisted of 9, 488 Finnish public-sector employees who retired in 2000–2011 and who reported their leisure-time and commuting physical activity before and after retirement. On average, participants provided data at 3.6 (of the four) repeat examinations during 10 years before and 10 years after the retirement. Physical activity was self-reported and was expressed as weekly metabolic equivalent task (MET) hours. Generalized estimating equations were used to examine physical activity trajectories around retirement. Results Among participants entering to statutory retirement physical activity first increased by 1.81 MET-hours (95 % confidence interval [CI] 1.20 to 2.42) during 4-year retirement transition, but then decreased by −1.80 MET hours (95 % CI −2.83 to −0.79) during the subsequent post-retirement period. Older retirement age, higher occupational status and fewer chronic diseases were associated with greater increase in physical activity during transition to statutory retirement. Conclusions Statutory retirement appears to be associated with a temporary increase in physical activity. Future research should examine ways to maintain the increased activity level after retirement.